2013
DOI: 10.1016/j.celrep.2013.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Motile Axonal Mitochondria Contribute to the Variability of Presynaptic Strength

Abstract: One of the most notable characteristics of synaptic transmission is the wide variation in synaptic strength in response to identical stimulation. In hippocampal neurons, approximately one-third of axonal mitochondria are highly motile and some dynamically pass through presynaptic boutons. This raises a fundamental question: Can motile mitochondria contribute to the pulse-to-pulse variability of presynaptic strength? Recently, we identified syntaphilin as an axonal mitochondrial docking protein. Using hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
213
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(226 citation statements)
references
References 33 publications
13
213
0
Order By: Relevance
“…We hypothesise that increased expression of Miro1 makes mitochondria more likely to arrest close to presynaptic terminals in response to local Ca 2+ as Miro1 overexpression increases mitochondrial trafficking 13, 14, 33 and mitochondria pass terminals more frequently. Thus, even rare Ca 2+ responses during TTX treatment might be sufficient to allow mitochondrial arrest when Miro1 is overexpressed, and therefore, a higher percentage of terminals are always occupied by a mitochondrion.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesise that increased expression of Miro1 makes mitochondria more likely to arrest close to presynaptic terminals in response to local Ca 2+ as Miro1 overexpression increases mitochondrial trafficking 13, 14, 33 and mitochondria pass terminals more frequently. Thus, even rare Ca 2+ responses during TTX treatment might be sufficient to allow mitochondrial arrest when Miro1 is overexpressed, and therefore, a higher percentage of terminals are always occupied by a mitochondrion.…”
Section: Resultsmentioning
confidence: 99%
“…Short-term plasticity is reduced [2,3,27] probably due to the Ca 2+ buffering capacity of mitochondria. Mitochondria passing by presynaptic boutons can cause changes in synaptic transmission [28]. The slow but continuous gain and loss of mitochondria at putative boutons we observed suggests that mitochondrion-induced synaptic effects will also occur in adult cortex but on a much slower timescale.…”
mentioning
confidence: 77%
“…Nonetheless, more sustained increases in energy demands may still preferentially deplete ATP from boutons lacking mitochondria. Indeed, after multiple rounds of electrical stimulation, Sun et al (55) found that the ATP/ADP ratio decreased more in boutons lacking mitochondria, despite having glucose present. In addition, we do not yet know whether regional energy failure between boutons also develops if the distance between mitochondria is pathologically increased (6).…”
Section: Discussionmentioning
confidence: 99%